Pengaruh Environmental Claims Dan Perceived Quality Terhadap Loyalitas Pelanggan Melalui Green Brand Image Produk Elektronik Home Appliances Di Sidoarjo - Chintya Rossalin; Donny Arif; Ramadhani Qurata A’yuni (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
The aim of this research is to examine the influence of Environmental Claims and Perceived Quality on Customer Loyalty with Green Brand Image as a mediating variable. This research uses a quantitative descriptive approach with a purposive sampling technique, with a total sample of 132 respondents who use household electronic products in the Sidoarjo area. Data collection was carried out through distributing questionnaires. The data analysis technique used is path analysis with the help of the SmartPLS program version 4.1.1.2. Based on the results of the data analysis carried out, it shows that Environmental Claims do not have a significant effect on Green Brand Image or Customer Loyalty. Perceived Quality has a positive and significant effect on Green Brand Image, but does not have a direct effect on Customer Loyalty. Green Brand Image has a positive and significant effect on Customer Loyalty, and is able to significantly mediate the relationship between Perceived Quality and Customer Loyalty. However, Green Brand Image does not mediate the relationship between Environmental Claims and Customer Loyalty. These findings confirm that perceptions of product quality and green brand image have an important role in forming customer loyalty, compared to just relying on environmentally friendly claims.